Drug repositioning: A bibliometric analysis - Sun, Guojun; Dong, Dashun; Dong, Zuojun; Zhang, Qian; Fang, Hui; Wang, Chaojun; Zhang, Shaoya; Wu, Shuaijun; Dong, Yichen; Wan, Yuehua (Frontiers in Pharmacology, 2022)
Drug repurposing has become an effective approach to drug discovery, as it offers a new way to explore drugs. Based on the Science Citation Index Expanded (SCI-E) and Social Sciences Citation Index (SSCI) databases of the Web of Science core collection, this paper presents a bibliometric analysis of drug repurposing publications from 2010 to 2020. Data were cleaned, mined, and visualized using Derwent Data Analyser (DDA) software. An overview of the history and development trend of the number of publications, major journals, major countries, major institutions, author keywords, major contributors, and major research fields is provided. There were 2978 publications included in the study. The findings show that the USA leads in this area of research, followed by China, the UK, and India. The Chinese Academy of Science published the most papers, and the NIH ranked first in the h-index. The Icahn School of Medicine at Mt Sinai leads in the average number of citations per paper. Sci Rep, Drug Discov. Today, and Brief. Bioinform. are the three most productive journals evaluated from three separate perspectives, and pharmacology & pharmacy are unquestionably the most commonly used subject categories. Cheng, FX, Mucke, HAM, and Butte, AJ are the top 20 most prolific and influential authors. Keyword analysis shows that in recent years, most research has focused on drug discovery/drug development, COVID-19/SARS-CoV-2/coronavirus, molecular docking, virtual screening, cancer, and other research areas. The hotspots have changed in recent years, with COVID-19/SARS-CoV-2/coronavirus being the most popular topic for current drug repurposing research.